CT Virtual Hysterosalpingography - Carrascosa, Patricia; Capuñay, Carlos; Sueldo, Carlos E.; Baronio, Juan Mariano (Springer International Publishing : Imprint: Springer, 2014)
This book provides a comprehensive review of CT Virtual Hysterosalpingography, a new non-invasive diagnostic technique that allows the evaluation of the entire gynecologic tract in a single study, by combining the benefits of hysterosalpingography (HSG) with multidetector Computed Tomography (CT). The addition of 64-row CT scanners with HSG has significantly improved visualization and assessment of the uterine cavity and fallopian tubes, and allows for the diagnosis of polyps, myomas, uterine anomalies and tubal pathology with a high degree of accuracy. CT Virtual Hysterosalpingography is written and edited by the leaders in the field and covers all aspects of the technique, from its origin and technical principles through to descriptions of the normal anatomy and most common pathologies. This will be an essential text for Gynecologists, Infertility Specialists, Radiologists and Reproductive Endocrinologists who would want to learn about this technique and how it can be implemented in their practice.